Surface acoustic wave (SAW) design and applications in microfluidics - Kishor, Rahul (2017)
Lab-on-a-chip (LOC) is the current trend towards developing point-of-care devices. LOC finds its application in fields of medicine, environmental monitoring and towards a multitude of industrial applications. It involves integrating all the functions that were done in a laboratory, from input samples to results delivery in an easy-to-handle device. This was realised due to the advent of microfluidics and the microelectronics technology. Physically, an LOC consists of four main parts: Microfluidics, actuators, sensors and readout circuits. Many research groups along with startup companies have developed technologies to realise fluid actuation/control and signal detection with impressive capabilities. However, there is a dearth of LOC’s available in the market. They are still confined within the spaces of the laboratory and regarded as a ”chip-on-lab” functionality, justifiably due to the lack of an integrated platform that performs the different assay procedures in a seamless and automated fashion. This work is in pursuit of developing an integrated platform to realise an LOC utilising surface acoustic wave (SAW) devices. SAW are nanometer amplitude vibrations that are generated on a piezoelectric substrate. During the last decade, SAW has been intensively used and researched for microfluidic applications majorly as an actuator. SAW capabilities as a sensor for immunoassay was also explored. This unique feature of SAW to act both as an actuator and sensor makes it easier for integration. In this thesis, we first study the use of SAW as an actuator of the fluids by establishing a novel mechanism for characterising the SAW energy transmission in fluidic channels, which is essential for all the SAW microfluidics design, using a mixing structure. We developed analytical models in this work that could be used to optimise the power transmission coefficient and hence increase actuation efficiency. Besides focusing on the application of SAW as an actuator, its usage as a sensor was primarily relying on the immunoassay technique which required complicated surface preparation steps. In the subsequent work, we proposed and demonstrated a new sensing methodology utilising photoacoustic induced surface acoustic wave (SAW-PA) for simultaneous optical and mechanical property characterization of analytes (including cells, nanoparticle and dyes). A nanosecond pulsed laser excitation on a sample triggers a longitudinal acoustic wave in the fluid which is mode converted into a Rayleigh SAW on the piezoelectric substrate and detected using the metal electrodes (interdigital transducer, IDT). We further developed a numerical model to study the wave conversion process (longitudinal acoustic waves to SAW) and demonstrate that the PA generated in the microfluidic channel acts as a mechanical resonator dependent on the dimensions of the microfluidic channel. We experimentally verified that a SAW device matched to the channel resonant frequency could improve the sensitivity. Finally, we propose a platform combining the SAW actuators and SAW-PA sensor, which is closer to realising the initial objective of an integrated platform for LOC. In this work, we have developed an integrated microfluidic system that combined high-efficiency (> 95%) tilted-angle standing surface acoustic wave (taSSAW) based particle separation, particle concentration inside an open microfluidic chamber and sensing, on a single LiNbO3 substrate. The platform demonstrated real-time quantitative detection of 10 μm polystyrene beads down to 7 particles in 10 μl of the sample volume in 15 minutes.